THE EFFECT OF SERVICE QUALITY, PRODUCT AND BRAND IMAGE ON CUSTOMER SATISFACTION BANK BNI LUBUK ALUNG - Mario, Muhammad Arief; Susanti, Febsri (LPPM Universitas Bina Bangsa, 2022)
Competition in banking companies is increasing to dominate market share created through customer satisfaction. Customers are the main factor for banks to gain trust from customers to continue using their services. This study aims to determine and analyze whether tangible, reliability, responsiveness, assurance, empathy, product and brand image affect customer satisfaction of Bank BNI Lubuk Alung, using a data collection method in the form of a questionnaire. The sample in this study were 99 respondents. In analyzing the data using validity, reliability, and classical assumption tests, namely normality, multicollinearity and heteroscedasticity. The analytical method used is multiple linear regression analysis, while for hypothesis testing, namely t-test with the help of SPSS. The results of the tests conducted found that: 1) Tangible has a positive and significant effect on customer satisfaction; 2) Reliability has a positive and significant effect on customer satisfaction; 3) Responsiveness has a positive and significant effect on customer satisfaction; 4) Assurance has a positive and significant effect on customer satisfaction; 5) Empathy has no significant effect on customer satisfaction; 6) Products has a significant effect on customer satisfaction; and 7) Brand image has a significant effect on customer satisfaction